2011
DOI: 10.1021/bi200964p
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of CF IA from Overexpressed Subunits Reveals Stoichiometry and Provides Insights into Molecular Topology

Abstract: Yeast Cleavage Factor I (CF I) is an essential complex of five proteins that binds signal sequences at the 3′ end of yeast mRNA. CF I is required for correct positioning of a larger protein complex, CPF, which contains the catalytic subunits executing mRNA cleavage and polyadenylation. CF I is composed of two parts, CF IA and Hrp1. The CF IA has only four subunits, Rna14, Rna15, Pcf11, and Clp1, but the structural organization has not been fully established. Using biochemical and biophysical methods, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 48 publications
4
34
0
Order By: Relevance
“…Our structure of the Rna14 HAT domain dimer is supported by published mutagenesis data on S. cerevisiae Rna14 (Gordon et al 2011), which showed that the R562E/Y563S double mutation disrupted its dimerization. These two residues are equivalent to Lys565 and Tyr566 of K. lactis Rna14 and are located in the center of the HAT domain dimer interface.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Our structure of the Rna14 HAT domain dimer is supported by published mutagenesis data on S. cerevisiae Rna14 (Gordon et al 2011), which showed that the R562E/Y563S double mutation disrupted its dimerization. These two residues are equivalent to Lys565 and Tyr566 of K. lactis Rna14 and are located in the center of the HAT domain dimer interface.…”
Section: Resultssupporting
confidence: 78%
“…This suggests that the linker between the HAT domain and the region at the C terminus of Rna14 that interacts with Rna15 is accessible to proteases and may be flexible. The flexibility of this linker has also been reported for the S. cerevisiae Rna14-Rna15 complex (Gordon et al 2011). The crystal structure of K. lactis Rna14 in crystal form 1 was determined at 2.8 Å resolution by the selenomethionyl single-wavelength anomalous diffraction (SAD) method (Hendrickson 1991).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To better understand how 3′-end processing signals are recognized to initiate 3′-end processing and transcription termination, we sought to obtain structural information on the complete CF I complex including Rna14, Rna15, Hrp1, and the pre-mRNA transcript. Unfortunately, crystallography has not been forthcoming with this complex, and EM studies still rely on low resolution approaches (24). Although the Rna14 and Rna15 complex has been studied biophysically (20) and by X-ray crystallography (25) and NMR (19), there is no complete structure with Hrp1.…”
Section: Resultsmentioning
confidence: 99%
“…According to the BioGRID database, there are seven interacting partners for Pcf11 identified by at least two experimental approaches, although some of these interactions might be mediated by another factor: Clp1, Rna14, Rna15, Rpo21, Ysh1, Ydh1, and Yra1. The middle region of Pcf11 helps in the assembly and localization of Rna14/Rna15 and Clp1 to the 3 ′ -UTR (Noble et al 2007;Qu et al 2007;Gordon et al 2011). Yra1 putatively interacts with Pcf11 through a region N-terminal to the very C-terminal zinc finger to facilitate assembly of the pre-mRNA for recognition by the RNA export machinery (Johnson et al 2009(Johnson et al , 2011.…”
Section: Discussionmentioning
confidence: 99%